Housekeeping and Plumbing: The Investability of Emerging Markets - Ladekarl, Jeppe; Zervos, Sara (World Bank, Washington, D.C., 2013)
The authors look at the investment allocation process employed by portfolio investors in emerging markets. In particular, they examine the first of a two-stage decision process: first, investors create a subset of countries with investments potential, to be analyzed later in further detail; second, they weigh expected returns versus risk and subsequently allocate their funds. The authors hypothesize that the determination of whether a country has potential investment opportunities, or not is influenced by a number of factors, especially related to size, quality of "housekeeping," (macroeconomic policies, political economy, local financial markets, corporate governance, and so on), and efficiency of "plumbing" (legal and regulatory framework, custody, clearing and settlement, taxes, and so on). By interviewing many types of these investors in both the United States and the United Kingdom, the authors delve into their decision-making processes, as well as attempt to uncover the factors they indicate, matter most in defining the "investment opportunities" universe. They determine the relative importance of such housekeeping, and plumbing factors while highlighting the role of external issues, such as index benchmarking and U.S. foreign policy. The authors recognize from the outset that the most profound effects on investment flows, or the required minimum expected returns, arise from improvements or deteriorations in macroeconomic policies. However, at the margin, improvements can be made in country policies that will, for a given macroeconomic situation, improve the ability of a country to attract international investment flows.